Digital Transformation in the Dynamics of Sharia Accounting Standards: Challenges and Opportunities in the Era of 4.0 and Society 5.0 - Chaniago, Nuraini; Nugroho, Lucky; Firdayetti, Firdayetti; Islami, Wardah; Igorevna, Volkhonova Mariya (Baca Dulu Publisher, 2024)
Digital transformation in the Industrial Revolution 4.0 and Society 5.0 era has presented opportunities and challenges in developing Sharia accounting standards. The phenomenon can be seen in the digital literacy gap, limited technological infrastructure, and the need to harmonize Sharia accounting standards with international standards such as IFRS. This research aims to analyze the dynamics of the development of Sharia accounting standards in the digital era, identify key challenges such as technological limitations and differences in interpreting Sharia principles, and uncover innovation opportunities through digitalization. A descriptive qualitative approach uses secondary data from academic journals, institutional reports, and regulatory documents. The study results show that blockchain, artificial intelligence (AI), and the Internet of Things (IoT) can improve Sharia-based finance's efficiency, transparency, and inclusion. However, its implementation requires infrastructure investment, increased digital literacy, and cross-sector collaboration. The implications of this research include strategic recommendations for regulators, practitioners, and academics to take advantage of digital technology opportunities to strengthen Islamic financial institutions' global competitiveness. The latest of this research lies in analyzing the integration of Sharia principles with modern technology, offering strategic guidance in creating relevant Sharia accounting standards in the digital era. This study provides important insights to encourage sustainability and innovation in Islamic financial management by Islamic principles.